Stronger and prolonged negative effects of one specific commercial organic fertilizer on an agrobiont spider compared with tillage and chemical fertilizer - Na Yu; Tianhong Xu; Fumin Shi; Weitong Wang; Ming Chen; Zewen Liu (Agriculture, Ecosystems & Environment, 2026)

Dissolution–recrystallization of zeolites: From chemical nature to structure reconstruction and functional engineering - Kaiwei Wang; Yihao Wang; Yi Zhai; Yan Chen; Jiaxing Zhang; Tongxue Zhang; Hao Ruan; Xuyang Zou; Qiao Sun; Qi Jiang; Mingshuai Sun; Tianlei Wang; et al. (Chemical Engineering Journal, 2026)

Efficient construction of active TiO6 species in TS-1 zeolite via treatment with amines and ammonium salts for enhanced cyclohexene epoxidation - Kaiwei Wang; Hao Ruan; Fumin Wang; Yi Zhai; Mingshuai Sun; Yan Chen; Jiaxing Zhang; Yihao Wang; Xuyang Zou; Xubin Zhang (Fuel, 2026)

Global synthesis of nitrogen management in sugarcane systems: Decoding climate-soil-management drivers of Brazil-China contrasts - Xiaomai Yuan; Shengsen Zhou; Fumin Wei; Li Ma; Yongfeng Sun; Dingjiao Peng; Run Liang; Yibao Luo; Baoshan Chen; Wei Yao; Ziting Wang (Field Crops Research, 2025)

Identifying hundredfold carbon emission gaps in multiple resource recycling routes of construction waste via process and hybrid life cycle assessment - Rui Chen; Haiyuan Wu; Junjie Li; Hao Wang; Lanxin Li; Linlin Sun; Fumin Ren (Waste Management, 2025)

Improved corn phenology monitoring using translation and weighting of characteristic points from time-series vegetation index - Qinyan Zhu; Fumin Wang; Siting Chen; Dailiang Peng; Qiuxiang Yi; Liming He; Zhanyu Liu (Computers and Electronics in Agriculture, 2025)

High-efficiency and stable perovskite solar cells via bidentate chelation for facet-engineered growth of FAPbI3 (111) crystals - Song Zhang; Yucong Zhou; Zhitao Shen; Yingying Li; Jian Song; Yicong Gao; Zezhi Wang; Bohao Zhang; Chong Chen; Rong Liu; Ying Liu; Ruirui Cao; et al. (Chemical Engineering Journal, 2025)

Insight into nitrogen removal through sulfate reducing anaerobic ammonia oxidation coupled with sulfur cycle: A comparative study on inorganic and organic conditions - Jiawei Li; Qianwen Sui; Fumin Zuo; Yiming Yang; Meixue Chen; Yuansong Wei (Journal of Environmental Management, 2025)

Simulation and experimental study on splitting performance of Rectifier Nozzle Type Critical Distributor for multi-parallel evaporators - Xiaofeng Li; Wenfu Zhang; Zhili Sun; Di Liang; Lei Yan; Haiwang Zhao; Jiale Chen; Fumin Hou; Xian Lv; Dandan Wang; Jiangman Yan (International Journal of Refrigeration, 2025)

Introducing Ce into the interface of NiCo LDH@PBAs to build multi core–shell electrode with superior stability of supercapacitor - Jiawei Wang; Jiacheng Li; Fumin Wang; Xubin Zhang; Xu Wu; Juan Zhang; Shuai Niu; Liang Chen (Chemical Engineering Journal, 2024)

A fast and efficient phenotyping method to estimate sugarcane stalk bending properties using near-infrared spectroscopy - Fumin Ma; Maoyao Wang; Ning Yan; Muhammad Adnan; Fuhong Jiang; Qian Hu; Guanyong He; Yinjuan Shen; Yan Wan; Yixian Yang; Shaojing Liang; Xiaoru Chen; et al. (European Journal of Agronomy, 2024)

Alternations of antibiotic resistance genes and microbial community dynamics on shared bicycles before and after pandemic lockdown - Leshan Xiu; Haodong Liu; Yi Xie; Qinqin Hu; Huimin Li; Fumin Chen; Chenxi Wang; Yuqian Zhang; Liyuan Hou; Kun Yin (Science of The Total Environment, 2024)

Improving the matching degree between remotely sensed phenological dates and physiological growing stages of soybean by a dynamic offset-adjustment strategy - Siting Chen; Qiuxiang Yi; Fumin Wang; Jueyi Zheng; Jiale Li (Science of The Total Environment, 2024)

Modeling soybean cultivation suitability in China and its future trends in climate change scenarios - Qinyan Zhu; Fumin Wang; Qiuxiang Yi; Xiaoyang Zhang; Siting Chen; Jueyi Zheng; Jiale Li; Tianyue Xu; Dailiang Peng (Journal of Environmental Management, 2023)

Thiolation modification of pectin effectively alleviates the weakening of wheat gluten network caused by natural pectin - Jinfeng Chen; Yanli Cui; Wanlu Shi; Fumin Yang; Yunxiang Ma; Shenggui Zhang; Yue Wang (Food Hydrocolloids, 2023)

Coordination number engineering of Zn single-atom sites for enhanced transfer hydrogenation performance - Yaping Song; Rou Guo; Binbin Feng; Yanghe Fu; Fumin Zhang; Yifei Zhang; De-Li Chen; Jiangwei Zhang; Weidong Zhu (Chemical Engineering Journal, 2023)

Detection of water-enriched goaf via the semi-airborne transient electromagnetic method - Chuantao Yu; Xi Zhang; Weiying Chen; Fumin Zhang; Zhongbin Tian (Journal of Applied Geophysics, 2023)

Physiological and Cytological Analyses of the Thousand-Grain Weight in ‘Zhongyan96-3’ Wheat - Luhua Li; Shuai Yang; Zhongni Wang; Mingjian Ren; Chang An; Fumin Xiong; Yuxuan Chen; Ruhong Xu (Journal of Plant Growth Regulation, 2023)

Compound treatment of thiolated citrus high-methoxyl pectin and sodium phosphate dibasic anhydrous improved gluten network structure - Jinfeng Chen; Yanli Cui; Shenggui Zhang; Yunxiang Ma; Fumin Yang (Food Chemistry, 2023)

Simultaneous interfacial and bulk defect passivation and interface energy band alignment optimization via In(SCN2H4)3Cl3 diffusion doping for inverted perovskite solar cells - Dong Yang; Yujuan Weng; Zhitao Shen; Mengqi Jin; Hu Shen; Qing Du; Jihong Zheng; Fumin Li; Chong Chen (Chemical Engineering Journal, 2023)

Simultaneous measurement of multiple labile heavy metals in soils by diffusive gradients in thin film technique - Rui Chen; Jiaxing Liu; Guoyu Ding; Fumin Ren; Rongguang Shi; Jungang Lv; Jing Cheng (Journal of Soils and Sediments, 2023)

pH-responsive in situ gelling properties of thiolated citrus high-methoxyl pectin and its potential gel mechanism - Jinfeng Chen; Yanli Cui; Fumin Yang; Shenggui Zhang; Yunxiang Ma; Jia Liu (Food Research International, 2023)

Streptomyces akebiae sp. nov., a novel actinomycete isolated from rhizosphere soil of Akebia trifoliate - Ping Mo; Kaiqin Li; Jinhua Zhou; Fumin Zhou; Yazhi Chen; Xiaojia Lin; Xiaoyu Liu; Kerui Huang; Wansheng Zou; Jian Gao (Antonie van Leeuwenhoek, 2022)

Overexpression of TaLAX3-1B alters the stomatal aperture and improves the salt stress resistance of tobacco - Luhua Li; Dingli Hong; Chang An; Yuxuan Chen; Pengpeng Zhao; Xin Li; Fumin Xiong; Mingjian Ren; Ruhong Xu (Molecular Biology Reports, 2022)

Multi-Sensor-Based Hierarchical Detection and Tracking Method for Inland Waterway Ship Chimneys - Fumin Wu; Qianqian Chen; Yuanqiao Wen; Changshi Xiao; Feier Zeng (Journal of Marine Science and Engineering, 2022)
In the field of automatic detection of ship exhaust behavior, a deep learning-based multi-sensor hierarchical detection method for tracking inland river ship chimneys is proposed to locate the ship exhaust behavior detection area quickly and accurately. Firstly, the primary detection uses a target detector based on a convolutional neural network to extract the shipping area in the visible image, and the secondary detection applies the Ostu binarization algorithm and image morphology operation, based on the infrared image and the primary detection results to obtain the chimney target by combining the location and area features; further, the improved DeepSORT algorithm is applied to achieve the ship chimney tracking. The results show that the multi-sensor-based hierarchical detection and tracking method can achieve real-time detection and tracking of ship chimneys, and can provide technical reference for the automatic detection of ship exhaust behavior.

Quantitative methods for predicting underground construction waste considering reuse and recycling - Rui Chen; Lanxin Li; Kai Yang; Fumin Ren; Chenggang Xi; Yang Lin; Hai Zheng (Environmental Science and Pollution Research, 2022)

Ecological risk assessment of heavy metals in farmland soils in Beijing by three improved risk assessment methods - Rui Chen; Xuying Cai; Guoyu Ding; Fumin Ren; Qi Wang; Nuo Cheng; Jiaxing Liu; Lanxin Li; Rongguang Shi (Environmental Science and Pollution Research, 2021)

Development of a colloidal gold-based immunochromatographic strip test using two monoclonal antibodies to detect H7N9 avian influenza virus - Fan Yang; Yixin Xiao; Bin Chen; Liyan Wang; Fumin Liu; Hangping Yao; Nanping Wu; Haibo Wu (Virus Genes, 2020)

An application of the LTP_DSEF model to heavy precipitation forecasts of landfalling tropical cyclones over China in 2018 - Zuo Jia; Fumin Ren; Dalin Zhang; Chenchen Ding; Mingjen Yang; Tian Feng; Boyu Chen; Hui Yang (Science China Earth Sciences, 2020)

Characteristics of tropical cyclone extreme precipitation and its preliminary causes in Southeast China - Wenyu Qiu; Fumin Ren; Liguang Wu; Lianshou Chen; Chenchen Ding (Meteorology and Atmospheric Physics, 2019)

Molecular characterization of H10 subtype avian influenza viruses isolated from poultry in Eastern China - Haibo Wu; Fan Yang; Fumin Liu; Xiuming Peng; Bin Chen; Linfang Cheng; Xiangyun Lu; Hangping Yao; Nanping Wu (Archives of Virology, 2019)

Development of a TaqMan MGB RT-PCR assay for the detection of type A and subtype H10 avian influenza viruses - Fan Yang; Bin Chen; Fumin Liu; Xiuming Peng; Tao Sun; Hangping Yao; Haibo Wu; Nanping Wu (Archives of Virology, 2018)

What makes the Sino‐Himalayan mountains the major diversity hotspots for pheasants? - Tianlong Cai; Jon Fjeldså; Yongjie Wu; Shimiao Shao; Youhua Chen; Qing Quan; Xinhai Li; Gang Song; Yanhua Qu; Gexia Qiao; Fumin Lei (Journal of Biogeography, 2018)
Aim The Sino‐Himalayas have higher species richness than adjacent regions, making them a global biodiversity hotspot. Various mechanisms, including ecological constraints, energetic constraints, diversification rate (DivRate) variation, time‐for‐speciation effect and multiple colonizations, have been posited to explain this pattern. We used pheasants (Aves: Phasianidae) as a model group to test these hypotheses and to understand the ecological and evolutionary processes that have generated the extraordinary diversity in these mountains. Location Sino‐Himalayas and adjacent regions. Taxon Pheasants. Methods Using distribution maps predicted by species distribution models ( SDM s) and a time‐calibrated phylogeny for pheasants, we examined the relationships between species richness and predictors including net primary productivity ( NPP ), niche diversity (NicheDiv), DivRate, evolutionary time (EvolTime) and colonization frequency using Pearson's correlations and structural equation modelling ( SEM ). We reconstructed ancestral ranges at nodes and examined basal/derived species patterns to reveal the mechanisms underlying species richness gradients in the Sino‐Himalayas. Results We found that ancestral pheasants originated in Africa in the early Oligocene (~33 Ma), and then colonized the Sino‐Himalayan mountains and other regions. In the Sino‐Himalayas, species richness was strongly related to DivRate, NPP , NicheDiv and colonization frequency, but weakly correlated with EvolTime. The direct effects of NicheDiv and DivRate on richness were stronger than NPP and EvolTime. NPP indirectly influenced species richness via DivRate, but its effect on richness via NicheDiv was relatively weak. Main conclusions Higher species diversity in the Sino‐Himalayas was generated by both ecological and evolutionary mechanisms. An increase in available niches, rapid diversifications and multiple colonizations was found to be key direct processes for the build‐up of the diversity hotspots of pheasants in the Sino‐Himalayan mountains. Productivity had an important but indirect effect on species richness, which worked through increased DivRate. Our study offers new insights on species accumulation in the Sino‐Himalayas and provides a useful model for understanding other biodiversity hotspots.

CASCIRE surveillance network and work on avian influenza viruses - Yuhai Bi; Weifeng Shi; Jianjun Chen; Quanjiao Chen; Zhenghai Ma; Gary Wong; Wenxia Tian; Renfu Yin; Guanghua Fu; Yongchun Yang; William J. Liu; Chuansong Quan; et al. (Science China Life Sciences, 2017)

Simulations of tropical cyclogenesis associated with different monsoon trough patterns over the western North Pacific - Xi Cao; Guanghua Chen; Tim Li; Fumin Ren (Meteorology and Atmospheric Physics, 2016)

Instantaneous-to-daily GPP upscaling schemes based on a coupled photosynthesis-stomatal conductance model: correcting the overestimation of GPP by directly using daily average meteorological inputs - Fumin Wang; Alemu Gonsamo; Jing M. Chen; T. Andrew Black; Bin Zhou (Oecologia, 2014)

Species delimitation in the C hinese bamboo partridge B ambusicola thoracica ( P hasianidae; A ves) - Chih‐Ming Hung; Hsin‐Yi Hung; Chia‐Fen Yeh; Yi‐Qiang Fu; De Chen; Fumin Lei; Cheng‐Te Yao; Chiou‐Ju Yao; Xiao‐Jun Yang; Yu‐Ting Lai; Shou‐Hsien Li (Zoologica Scripta, 2014)
Although tropical and subtropical Asia harbour a high level of species diversity, their species richness can be underestimated because species which are in fact distinct have not been separately identified. In this study, we delimit B ambusicola thoracica into two full species, the Chinese bamboo partridge ( B. thoracica ) in continental Asia and the Taiwanese bamboo partridge ( B . sonorivox ) on the island of Taiwan, using coalescent‐based multilocus division and diagnosable vocalization patterns. Isolation‐with‐migration analysis indicated that the two bamboo partridges diverged approximately 1.8 million years ago, with gene flow present most probably during the early stages of their divergence. This conclusion supports the hypothesis that diverging lowland lineages spread across the Asian mainland, and continental islands have more opportunities for secondary contact than highland ones when the sea level was low. Our results imply that conservation of biodiversity in tropical and subtropical Asia could be hindered by overlooking numerous ‘hidden’ species and highlight the importance of re‐examining the taxonomic statuses of species in this region traditionally defined as polytypic.

Isolation and Characterization of 14 Polymorphic Microsatellite Loci in the Big-Headed Turtle (Platysternon megacephalum) - Liushuai Hua; Fumin Wang; Shiping Gong; Yan Ge; Guoling Chen; Jinping Chen (Biochemical Genetics, 2014)

Variation in baseline corticosterone levels of Tree Sparrow (Passer montanus) populations along an urban gradient in Beijing, China - Shuping Zhang; Fumin Lei; Shenglin Liu; Dongming Li; Cong Chen; Peizhe Wang (Journal of Ornithology, 2011)

Impacts of the MJO on winter rainfall and circulation in China - Xiaolong Jia; Lijuan Chen; Fumin Ren; Chongyin Li (Advances in Atmospheric Sciences, 2011)